Estimating Catabolism: A Possible Tool for Nutritional Monitoring of Patients With Acute Kidney Injury - Bufarah, Marina Nogueira Berbel [UNESP]; de Góes, Cassiana Regina [UNESP]; Cassani de Oliveira, Mariana [UNESP]; Ponce, Daniela [UNESP]; Balbi, André Luis [UNESP] (Elsevier, 2017)
Hypercatabolism has been described as the main nutritional change in acute kidney injury. Catabolism may be defined as the excessive release of amino acids from skeletal muscle. Conditions such as fasting, inadequate nutritional support, renal replacement therapy, metabolic acidosis, and secretion of catabolic hormones are the main factors that affect protein catabolism. Given the imprecision of the methods conventionally used to assess and monitor the nutritional status of hospitalized patients, the parameters of protein catabolism, such as nitrogen balance, urea nitrogen appearance, and protein catabolic rate appear to be the main measures in this population. Considering the high prevalence of malnutrition in this population and important limitations in this clinical condition, such as the inflammatory state and altered fluid, catabolism parameters are accurate and reliable methods that could contribute to minimize adverse prognosis in this population.